Effect of injection timing and EGR on engine-out-responses of a common-rail diesel engine fueled with neat biodiesel - Teoh, Y.H.; Masjuki, Haji Hassan; Kalam, M.A.; How, H.G. (Royal Society of Chemistry, 2015)
Nowadays, diesel-powered engines are becoming attractive worldwide due to their superior fuel economy, higher efficiency and excellent reliability. Biodiesel can be considered as the most promising and in demand alternative fuel because it is a non-toxic, biodegradable and renewable fuel. This work attempts to simultaneously reduce the BSNOx and smoke from the levels of fossil diesel by using palm methyl ester (PME) biodiesel. In addition, this paper describes the conversion of a common-rail injection system with a custom-made electronic control system, focusing on hardware development, the engine control unit and fuel delivery system development. Parametric studies dealing with injection timing and exhaust gas recirculation (EGR) variation using neat palm biodiesel were performed and compared with baseline diesel. The tests were performed at a constant speed and load of 1500 rpm and 0.4 MPa, respectively. Firstly, the start of injection (SOI) timing was varied from TDC to -25° ATDC to demonstrate the flexible control of the custom-made engine controller. Later, the SOI timing was kept at an optimum of -11°ATDC and the EGR rates were adjusted (i.e. 0-50%). The experimental results indicated that both the injection timing and EGR variation had a prominent effect on the engine performance, emissions and combustion characteristics for an engine operating with baseline diesel or neat biodiesel. Based on the highest brake thermal efficiency (BTE) and a reasonable NOx level, the optimum injection timing is found to be at -11°ATDC for both the baseline diesel and biodiesel operation. A wider range of EGR rates from 0% to 50% were investigated to bring down the NOx levels from the EURO II limit to meet with more stringent EURO limits. It was found that with the PME fuel, engine operation at 30% EGR resulted in the optimum trade-off between BSNOx and smoke emissions. In fact, simultaneous BSNOx and smoke reduction from the levels of fossil diesel is possible with the use of PME biodiesels in parallel with the implementation of late SOI timing or a higher EGR rate in diesel engines.